KEWENANGAN MAHKAMAH KONSTITUSI PADA SENGKETA HASIL PEMILIHAN KEPALA DAERAH - Putu Tantry Octaviani; I Gusti Ngurah Parikesit Widiatedja (Kertha Negara : Journal Ilmu Hukum, 2015)
This writing shall be entitled as “The Authority of The Constitutional Court on The Result of Local Election’s Dispute